Development of a flow method for the determination of phosphate in estuarine and freshwaters - Comparison of flow cells in spectrophotometric sequential injection analysis - Mesquita, Raquel B. R. (2012)
A sequential injection system with dual analytical line was developed and applied in the comparison of two different detection systems viz; a conventional spectrophotometer with a commercial flow cell, and a multi-reflective flow cell coupled with a photometric detector under the same experimental conditions. The study was based on the spectrophotometric determination of phosphate using the molybdenum-blue chemistry. The two alternative flow cells were compared in terms of their response to variation of sample salinity, susceptibility to interferences and to refractive index changes. The developed method was applied to the determination of phosphate in natural waters (estuarine, river, well and ground waters). The achieved detection limit (0.007 mu M PO43-) is consistent with the requirement of the target water samples, and a wide quantification range (0.024-9.5 mu M) was achieved using both detection systems.